Analisis Pembelajaran Daring Sebagai Upaya Menuju Paperless Policy Di Lingkungan Kampus FKIP, Universitas Sultan Ageng Tirtayasa - Enggar Utari; Mahrawi Mahrawi; Rani Mahadika Gumanti (Universitas Muhammadiyah Luwuk, 2022)
The outbreak of the Covid-19 pandemic has an impact on the transition of the learning system, namely from learning in the class to virtuallearning or commonly known online learning. During the process, online learning uses technology more than using paper. The use of technology has a positive impact on the environment in the form of a decrease in the amount of paper waste produced in the surrounding environment. From the reduced amount of waste, a policy called the paperless policy. Therefore, an analysis related to online learning during the Covid-19 pandemic was carried out as an effort towards a paperless policy.The purpose of this study was to determine the level of use of technology and use of paper among students during online learning during the Covid-19 pandemic. Qualitative descriptive research method by distributing questionnaires to students at the FKIP campus, Sultan AgengTirtayasa University. Sampling was done by purposive sampling.The results obtained from this study are 99% of respondents admitted that they use paper less when carrying out learning and use technology more. Thus, the FKIP campus of Sultan AgengTirtayasa University is declared ready to move towards a paperless policy. Keyword:Paperless Policy, Online Learning, Paper Usage, Covid-19 Pandemic.